A Flexible Solid-State Pulsed Power Topology - Davari, P.; zare, F.; Ghosh, Arindam (Institute of Electrical and Electronics Engineers ( IEEE ), 2012)
Advances in solid-state switches and power electronics techniques have led to the development of compact, efficient and more reliable pulsed power systems. This paper proposes an efficient scheme that utilizes modular switch-capacitor units in obtaining high voltage levels with fast rise time (dv/dt) using low voltage solid-state switches. The proposed pulsed power supply has flexibility in terms of controlling energy and generating broad range of voltage levels. The energy flow can be controlled as the stored energy can be adjusted by a current source utilized at the first stage of the system. Desirable voltage level can be obtained by connecting adequate number of switch-capacitor units. Moreover, the proposed topology is load independent. Therefore it can easily supply wide range of applications especially the low impedance ones. The effectiveness of the proposed approach is verified by simulations.